Hierarchical Distribution of Rural Settlement in Kolhapur District: A Geospatial Analysis (International Journal of Food and Nutritional Sciences, 2022)
The Indian settlement system is typically a village system. The village community has beenessentially an agro-craft community the economic organization based on the local soil, animal andplant world and their simple utilization at direct subsistence level. Here an attempt has been made tounderstand the settlement system and its evolution to the present context.